â€œALâ€ AL-DAKHILIYAH â€˜ALA AL-ASMAâ€™: DIRASAH TAHLILIYAH NAHWIYAH FI SURAH YASIN - Ubaidillah, Ubaidillah (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2018)
This research discusses Nahwu that can help improve the understanding of the Qur'an, especially the surah Yaasin in which the type of